2019
DOI: 10.1128/msystems.00217-18
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Patterns of Yersinia pestis and Yersinia pseudotuberculosis during Infection and Biofilm Formation in the Flea Digestive Tract

Abstract: Yersinia pestis, the etiologic agent of plague, emerged as a fleaborne pathogen only within the last 6,000 years. Just five simple genetic changes in the Yersinia pseudotuberculosis progenitor, which served to eliminate toxicity to fleas and to enhance survival and biofilm formation in the flea digestive tract, were key to the transition to the arthropodborne transmission route. To gain a deeper understanding of the genetic basis for the development of a transmissible biofilm infection in the flea foregut, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 100 publications
(127 reference statements)
0
11
0
Order By: Relevance
“…Fleas are blood-feeding arthropods that are vectors of several Gram-negative bacterial pathogens including Bartonella spp., Rickettsia felis, Rickettsia typhi, and Yersinia pestis [1]. Once ingested by a flea, the bacteria must overcome insect immunity, establish a replicative niche in the gut, and alter their gene expression to promote survival and transmission [2][3][4][5][6][7][8]. For Y. pestis, infection is initiated when fleas ingest blood from a highly bacteremic animal, typically a rodent.…”
Section: Introductionmentioning
confidence: 99%
“…Fleas are blood-feeding arthropods that are vectors of several Gram-negative bacterial pathogens including Bartonella spp., Rickettsia felis, Rickettsia typhi, and Yersinia pestis [1]. Once ingested by a flea, the bacteria must overcome insect immunity, establish a replicative niche in the gut, and alter their gene expression to promote survival and transmission [2][3][4][5][6][7][8]. For Y. pestis, infection is initiated when fleas ingest blood from a highly bacteremic animal, typically a rodent.…”
Section: Introductionmentioning
confidence: 99%
“…pseudotuberculosis during infection in the flea digestive tract revealed that the expression of the Y . pseudotuberculosis T6SS4 system, including the rovC homologous gene is strongly upregulated during flea infection compared to in vitro growth [ 66 ]. It is still unclear how the different regulators and regulatory circuits are integrated and coordinated to produce active T6SS4 when needed.…”
Section: Discussionmentioning
confidence: 99%
“…fleas, flies) and RovC homologues are found in several insect and plant pathogens (S4A Fig), it is likely that the Yersinia T6SS4 system, besides its described role during infection of mammals [21], is important in the species' native environment. In fact, a recent study comparing gene expression patterns of Y. pestis and Y. pseudotuberculosis during infection in the flea digestive tract revealed that the expression of the Y. pseudotuberculosis T6SS4 system, including the rovC homologous gene is strongly upregulated during flea infection compared to in vitro growth [66]. It is still unclear how the different regulators and regulatory circuits are integrated and coordinated to produce active T6SS4 when needed.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Primer 5.0 was used to design the primer ( Table 1 ). RT-PCR was performed according to previous studies [ 14 18 ].…”
Section: Methodsmentioning
confidence: 99%